Getting serious with ipads: The intersection of game design and teaching principals - Masek, M.; Murcia, Karen; Morrison, J. (ACCE - Journal for the Australian Council for Computers in Education, 2013)
Mobile devices, such as tablets and smart phones, are increasingly being utilised as tools for education, with tablets such as the Apple iPad being introduced into many classrooms. These devices are seen as enablers of learning through a fun, interactive interface; however the process of producing a pedagogically valid, yet entertaining application is often poorly understood. This problem motivated the authors to work collaboratively on the design and development of an iPad game targeted at foundation level classrooms and linked to the Australian science curriculum. In this paper we review the tools and processes that are available for the production of educational games. We begin by reviewing the technology and development paths available for targeting a variety of mobile platforms. Following this, we examine theories of game design as applied to educational settings. This review frames our discussion of the design features of the iPad game "Aussie Explorers" produced as an outcome of the project.